The Effect of Character Competency and Intensity of Virtual Item Purchases on the Financial Management of the Indonesian PUBG Mobile Game - Ninik Marera; Dedi Mulyadi; Santi Pertiwi Hari Sandi (International Journal of Economics and Management Research, 2025)
This study aims to analyze the influence of character competencies and the intensity of virtual item purchases on the financial management of PUBG Mobile players in Indonesia. Character competencies are studied through indicators of discipline, responsibility, investment, driving factors and self-control. Meanwhile, the purchase intensity of virtual items is measured based on the frequency of purchases, the number of items purchased, the level of satisfaction, the desire to buy, and the type of items purchased, such as skins, weapons, and clothing. A descriptive-verifiable approach was used in this study, with a structured questionnaire distributed to 61 active PUBG Mobile players who had purchased virtual items. Data analysis was conducted using SmartPLS 4 to evaluate the validity and reliability of the measurement model, as well as identify the relationships and significance between variables. The results showed that character competence and the intensity of purchasing virtual items significantly affected players' financial management practices. Players with a higher level of character skill tend to have good discipline and self-control, which allows them to manage the game budget more efficiently and not spend too much. In contrast, intensive purchasing behaviors are associated with increased awareness of financial limits, where players adjust their spending habits to balance in-game needs and real-life priorities. This research emphasizes how important character competencies are to encourage players to make wise financial decisions. The study also emphasizes how important it is for players to understand how their purchasing intensity is, which can help them make better financial planning